A Thai Psychiatrist’s work experience in the Republic of Maldives - Tantiphlachiva, Kasem (Journal of the Psychiatric Association of Thailand, 2023)
The author worked as a specialist in psychiatry in the Republic of Maldives from May 25 to June 25, 1994 on a Thai – Maldives cooperative project. The author gave psychiatric aid to medical personnel and gave psychiatric services to the people at the Central Hospital in Male and at Kuraidhu Rehabilitation Centre for the Aged and the Disabled Persons.